2014
DOI: 10.1017/s0021932014000017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2011 Earthquake on Marriages, Births and the Secondary Sex Ratio in Japan

Abstract: On 11th March 2011 a magnitude nine earthquake struck the Tohoku region of Japan. The earthquake resulted in a large tsunami and an accident at the Fukushima Nuclear Power Plant. Previous studies have suggested that demographic indices relating to reproduction and marriage change after such massive disasters (e.g. large earthquakes). The present study investigated whether the number of births, number of marriages and the secondary sex ratio (SSR) changed after the East Japan Earthquake. The monthly number of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 19 publications
3
50
0
Order By: Relevance
“…Torche & Kleinhaus (2012) showed that stress exposure, particularly in early pregnancy, was associated with a lower SSR. Our finding that the SSR was lower than the expected range at 7 months after the 2011 earthquake (Hamamatsu et al, 2014) was consistent with previous studies. It suggests that experiencing an earthquake in months two or three of gestation may result in a significant decline in the SSR.…”
Section: Sex Ratiosupporting
confidence: 93%
See 1 more Smart Citation
“…Torche & Kleinhaus (2012) showed that stress exposure, particularly in early pregnancy, was associated with a lower SSR. Our finding that the SSR was lower than the expected range at 7 months after the 2011 earthquake (Hamamatsu et al, 2014) was consistent with previous studies. It suggests that experiencing an earthquake in months two or three of gestation may result in a significant decline in the SSR.…”
Section: Sex Ratiosupporting
confidence: 93%
“…O'Donnell & Behie (2014) noted the possibility of a small increase in marriage rates in 2012 in some disaster-stricken prefectures. To confirm their observation, we evaluated the total number of marriages in 2012 (10-21 months after the 2011 earthquake) in four different geographical areas: the whole of Japan, the disaster-stricken area, the non-disaster-stricken area and each prefecture (n ¼ 47), and performed a quadratic regression analysis, which was also used in Hamamatsu et al (2014). Table 1 shows that the total number of marriages recorded in 2012 fell within the range of the 95% confidence limits (CL) for the predicted mean number of marriages in the whole of Japan, the disaster-stricken area and the non-disaster-stricken area.…”
Section: Marriagementioning
confidence: 99%
“…The decreased number of births from December 2011 to June 2012 in the 13 prefectures affected by the Great East Japan Earthquake and the FDNPP disaster (including Fukushima prefecture) was reported by a previous study. 3 However, as its authors acknowledged clearly, only a short period (7 months) was examined. In contrast, the present study examined a period of 11 years and identified long-term trends in birth rates using an interrupted time series design.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study showed that the number of births decreased in the 13 prefectures affected by the Great East Japan Earthquake and the FDNPP disaster (including Fukushima prefecture) between December 2011 and June 2012. 3 On the other hand, mass media reported that, while there was a slight recovery in the number of births in Fukushima Prefecture 2 years after the disaster (in 2013), the numbers decreased again in 2016 based on vital statistics in the prefecture. 4 , 5 However, whether or how the trend in birth rates in the Fukushima Prefecture changed after the disaster has not been examined thoroughly in the extant literature.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that the number of births declined in Japan after the 2011 disaster at the national level (ie, irrespective of proximity to the affected area). 3 Given the strong interest in increasing the birth rate in Japan and in other developed countries, and the fact that any country with nuclear power plants can potentially be affected by a nuclear accident like Japan, it is critically important to understand how a nuclear accident and radiation contamination affect women’s perceptions and decisions about future pregnancy.…”
Section: Introductionmentioning
confidence: 99%